Malaysian style corndog / Dina Aliya Abd Kahar ...[et al.] - Abd Kahar, Dina Aliya; Malek, Siti Nurbadrina; Nordin, Nazmi Naim; Mohd Adzli, Muhammad Fariszul Haikal; Mohd Azri, Fakhrul Azim (2022)
Assignment 3 is the business plan that concentrates on the management and entrepreneurial element of starting a new business. In this assignment our group planned to open a shop and sell Corndog. Our business name is named Malaysian Corndog Style. Malaysian Style Corndog sells a corndog with variety of coating which customers can choose based on their preference and our aim is to fulfil our customer needs. The ingredients that Malaysian Style Corndog uses are high quality ingredient. Malaysian Style Corndog intends to open its first branch at Jonker Street , Melaka in 2022 as there is a potential of having good sales as the number of residents and who live and work there are very high. It is also one of the main attractions in Melaka. Malaysian Style Corndog is a partnership business that consists of 5 members. Malaysian Style Corndog will provide a friendly, comfortable atmosphere where the customer can receive quality food and service at a reasonable price. Apart from that, we also wanted to widely introduce new menus as ideas with trending vibes. Malaysian Style Corndog will be open from 12pm to 9.00 pm where usually people will find a snacks before having a lunch and it will operate on Monday until Saturday. These products are considered marketable as it will satisfy the market’s target needs which are most of them are local resident and tourists. In the future, Malaysian Style Corndog is also planning on opening new branches of shop at places around the country. This is important as to increase more profit as well as share our exotic products to more people.